2008
DOI: 10.1112/plms/pdn019
|View full text |Cite
|
Sign up to set email alerts
|

Cohomology and support varieties for Lie superalgebras II

Abstract: In [2] (Preprint, 2006, arXiv:math.RT/0609363) the authors initiated a study of the representation theory of classical Lie superalgebras via a cohomological approach. Detecting subalgebras were constructed and a theory of support varieties was developed. The dimension of a detecting subalgebra coincides with the defect of the Lie superalgebra, and the dimension of the support variety for a simple supermodule was conjectured to equal the atypicality of the supermodule. In this paper the authors compute the sup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…Proof. The second equality is immediate from [BKN3, Theorem 2.9.1(c)] and [BKN1,Proposition 5.2.2]. We now consider the first equality.…”
Section: A Categorical Invariantmentioning
confidence: 95%
“…Proof. The second equality is immediate from [BKN3, Theorem 2.9.1(c)] and [BKN1,Proposition 5.2.2]. We now consider the first equality.…”
Section: A Categorical Invariantmentioning
confidence: 95%
“…Supergroups, Lie superalgebras, and related Z 2 -graded structures (including Z-graded Hopf algebras as defined by Milnor and Moore [39]) thus provide another natural setting for geometric methods. With Boe and Nakano, the second author initiated a study of support varieties for complex Lie superalgebras and showed that they capture information about the representation theory of these algebras, including atypicality, complexity, and the thick tensor ideals of the category [12][13][14][15]. In independent work, Duflo and Serganova [20] also defined associated varieties for Lie superalgebras in characteristic zero and showed they too provide representation theoretic information.…”
Section: Introductionmentioning
confidence: 99%
“…The category F has enough projectives ( [3]), is self-injective ( [4]), meaning that a module is projective if and only if it is injective, and for Type I classical Lie superalgebras, e.g. gl(m|n), F is a highest weight category ( [2]).…”
Section: Introductionmentioning
confidence: 99%